RANCANGAN DAN IMPLEMENTASI GALERI VIDEO DAN ANIMASI PADA SITUS LAPAN POLAR SATELLITE - Soewarto Hardhienata; Medria Kusuma Dewi (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2009)
Lapan Tubsat satellite has produced large number of videos or satellite images since the first launch from the Satish Dhawan Space Center, Sriharikota India, on January 10, 2007. LAPAN expect that the results of the satellite tracking needs a storage media that enables it to be more accessible and attractive to the public. Therefore, a facility is designed and implemented to meet the user requirements. The built of an interactive video gallery which is embedded with the site is the main focus of this paper. In addition, animations and video player are also implemented so that Lapan Polar Satellite Sites (SLPS) become more interactive and interesting to the site visitors.